INFLUENCE OF INFORMATION QUALITY, SYSTEM QUALITY, SERVICE QUALITY AND SECURITY ON USER SATISFACTION IN USING E-MONEY BASED PAYTREN APPLICATIONS - winanda wahana wargadalam (Pusat P2M Politeknik Negeri Batam, 2019)
Nowadays technology grow extremely fast and it is helpful in communication and transactions, this effect to human behavior that people consider using technology intentively in daily activites cause of its facilities, one of facilities is digital economic transactions or e-money. Due to increasing of technology, there are some companies run their business form e-money based applications, one of the applications is the PayTren. The purposed of this research is to examine the satisfactory of the user who apply PayTren applications, such as the influence of information quality, system quality, service quality and security. The method of the research is based on DeLone and McLean models, then it will be modified. The research’s data is quantitative data. researchers collected 89 questionnaires from the population of PayTren application users in Batam by using a purposive sampling technique. The conclusion of the research show that there is an influence between the quality of information, service quality and security on the satisfaction of e-money users based on the PayTren application, while it is found that there is no influence between the quality of the system on the satisfaction of e-money users based on PayTren applications.